Sistem Rekomendasi Wisata Di Kota Batu Dengan Metode Voting Borda Berdasarkan Metode TOPSIS Dan PROMETHEE - Rivaldy Raihan Syams; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Batu City is one of the destinations for traveling. Traveling is an activity to travel, both individually or in groups with the aim to expand knowledge, have fun and so on. Traveling can also ease the burden of mind stress after carrying out high work activities. Batu City has many tourist sites that can be visited. With so many tourist locations, to determine the location of tourism that suits your tastes and interests, it is necessary to do an in-depth search of tourist activities, quality of tourism and tourist safety that can take a lot of time. Therefore, system is needed to obtain a ranking of tourist sites according to their tastes and interests based on the criteria that have been determined namely the group decision support system using the TOPSIS, PROMETHEE and Borda methods. TOPSIS and PROMETHEE methods are used for decision making by decision makers. Borda method is used for group decision making from the results of each method of decision making by the decision maker